2015
DOI: 10.7848/ksgpc.2015.33.5.373
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Reorganization of the National Spatial Information System

Abstract: Spatial information has been widely used for efficient land use and management, disaster management, environment management, infrastructure management, corporate marketing, and cultural assets management, and the need for spatial information is expected to be increased. For this reason, central government, local government and public institutions must establish a National Spatial Information System (Fifteen systems related to spatial information managed by National Spatial Data Infrastructure Policy office, NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The combination of preprocessed UAV multispectral data and SSC estimation algorithm based on field observation data enables monitoring of SSC spatial distribution in a wide range. However, due to the limitations of georeferencing on water surface, existing UAV-based water quality studies have either necessarily included land (rivers and lakes) within the observation range or have only performed qualitative analysis without coordinate referencing [36,46,50]. In this study, it was demonstrated that projection of a UAV's data sequence on the water surface is possible through direct georeferencing using the IMU and GPS information mounted on the UAV.…”
Section: Ssc Mapping Through Uavsmentioning
confidence: 92%
See 1 more Smart Citation
“…The combination of preprocessed UAV multispectral data and SSC estimation algorithm based on field observation data enables monitoring of SSC spatial distribution in a wide range. However, due to the limitations of georeferencing on water surface, existing UAV-based water quality studies have either necessarily included land (rivers and lakes) within the observation range or have only performed qualitative analysis without coordinate referencing [36,46,50]. In this study, it was demonstrated that projection of a UAV's data sequence on the water surface is possible through direct georeferencing using the IMU and GPS information mounted on the UAV.…”
Section: Ssc Mapping Through Uavsmentioning
confidence: 92%
“…TriOS RAMSES [45] is a hyperspectral sensor with 256 channels for the UV-Vis wavelength band (320-950 nm) and is a high-precision radiometer used for monitoring land and water quality. Kim et al [46] showed that the radiance and irradiance had lower spectral values in the NIR wavelength band of RedEdge than in the TriOS RAM SES; however, their differences were negligible in most bands. Thus, RedEdge can obtain 2D ocean color observations instead of the TriOS RAMSES.…”
Section: In Situ Spectral Measurements For the Water Surfacementioning
confidence: 99%